« Salvation addiction » : vers une vision post-confessionnelle de la mère dans la poésie de Sharon Olds - Erik MARTINY (E-REA)
After having outlined what I call the Athena complex thematized in Sharon Olds’s poetry, this article attempts to shed some light on the sizeable number of poems Olds has devoted to mother figures as her monstrous depictions of the father have caused criticism of her work to focus exclusively on representations of the father. Within the framework of this subject matter, Olds’s aesthetic is contextualized by the postconfessional trend in American poetry.